DESAIN ROGOWSKI COIL UNTUK PENGUKURAN ARUS PETIR 30 KA DAN 100 KA PADA TOWER TELEKOMUNIKASI - Priyono, Hendry
ABSTRACT Lightning is a natural phenomenon that often occurs, especially in tropical countries like Indonesia. This is due to Indonesia's position on the equator so that the number of lightning that happen is more than other sub-tropical countries. Also, the current of lightning strikes in Indonesia is greater. Lightning strikes will be very dangerous and cause damage to infrastructure such as buildings and disruption of communication systems if not properly anticipated. Therefore, the measurement of the lightning strike current is important. Currently, there are many tools used to measure the current of a lightning strike. However, most of the tools does not have enough capacity so they cannot be used to measure the high current of a lightning strike. In this study, we will discuss the design of the Rogowski coil as a tool for measuring the current of a lightning strike with the ability to detect lightning up to 100 kA. The Rogowski coil is a toroidal coil of wire with an air core and works using the principle of electromagnetic to measure current. The Rogowski coil was chosen because this tool has several advantages such as does not have saturation so that the results of the lightning current measurement obtained will remain linear, inexpensive and flexible. At the output of the Rogowski coil, a conditioning circuit consists of amplifier circuits, an integrator (filter for low frequencies) and a phase shifter. Then the output of the circuit is connected to an oscilloscope to see the measurement results. The data obtained from lightning current measurements can be used to determine the accuracy of the tool and later become a reference for the installation of a better lightning protection system in Indonesia. We hope in the future, there will be no more damage to infrastructure due to lightning strikes caused by failure of the protection system. Keywords: Lightning Current, Measurement, Rogowski coil.